Aspects of the Organizational Field in the University Policlinic. - Jorge Cañellas Granda; Maricel Castellanos González; Carmen Niurka Piña Loyola; Asbely Yera Sánchez; Iraldo Mir Ocampo; Zenia Sánchez García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
The study of the organizational field is of great importance, because it constitutes an essential element in the development of the managerial strategy of an institution, facilitating the directive a perspective vision of the organization and a diagnostic element of reality. The conversion of our policlinics in universities implies substantial changes in the organizational field, which impact directly the teaching-learning process. Starting from the dialectical materialistic approach and by means of the induction-deduction methods, the analysis and the synthesis, everything supported it in the bibliographical revision, our objective is to establish the dimensions of this field and its relationship with this process.